PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN EDUCANDY PADA TOPIK KEGIATAN JUAL BELI SEBAGAI SALAH SATU CARA PEMENUHAN KEBUTUHAN - Muthia Ratna A; Elly Sukmanasa; Dendy Saeful Zen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Development of Learning Evaluation Using Educandy on the Topic of Buying andSelling Activities as a Way to Meet the Needs of Grade IV Students. This researchwas conducted at East Cilendek State Elementary School 2, in the even semesterof the 2024/2025 school year. The method in this study uses the Research andDevelopment (R&D) method with the ADDIE (Analysis, Design, Development,Implementation, and Evaluation) development model. This research involved 31students and carried out a validation process and a learning evaluation trial that hadbeen developed. Validation was carried out by four validation experts, namely mediaexperts, linguists, material experts (lecturers), and material experts (teachers).Based on the results of the validation that has been carried out by the validators,namely 96% media experts, 92% linguists, 98% material experts (lecturers), and84% material experts (teachers) with an average result of 92.5% are included in the“Very Feasible” criteria. The results of the test conducted by the students resultedin a final score with an average of 90.25%. This shows that learning evaluation usingeducation and buying and selling activities as one of the ways to meet needs is veryfeasible to use as learning product.